(untitled) (Journal on studies and research of academic knowledge, 2022)
De facto unions are a consolidated reality in Paraguay and as the years go by, there are the people who, for various reasons, choose this way of life to form a family. The de facto union or concubinage is legislated in Law 1/92, of partial reform of the Civil Code, in articles 83 to The conditions are that each one, the man or the woman, live together, but above all have possibility of getting married. The objectives of this research work were: to determine the possible hereditary rights between the cohabitants, study the succession regulation in general of the de facto union and analyze the regulations for factual unions, for which a non- experimental qualitative approach has been used, descriptive scope and documentary analysis technique. The main results reached indicate that the partner is in a state of defenselessness when the requirement to demonstrate the existence of the bond through a trial other than the succession, could cause damage to free access to the inheritance.